Investigação de ações em sustentabilidade em universidades públicas federais nos eixos água, energia e resíduos - Pereira, Iara Ivana (Universidade Federal de São Carlos, 2022)
Aware of the energy potential of municipal solid waste (MSW), the challenges envisaged for cleaner technologies and the desire that Higher Education Institutions (HEIs) to play the role of developing professionals and technologies to solve the problems demanded by society, in this paper aimed to understand the issue about sustainability and development sustainable, in addition to identifying the actions in sustainable developed by federal public HEIs, in the compartments: water, energy and waste. Thus, to understand the debate around the environmental issue, a bibliographic survey was carried out and, in order to understand how universities have acted in favor of sustainability, federal public HEIs were selected, totaling 69 institutions, so that the actions carried out could be investigated in the selected compartment. In this way, a consultation was carried out on the websites of the institutions, using some keywords. Then, in dialogue with the waste compartment, studies related to three public universities, two State Universities and one federal, which are: UEL, USP campus São Paulo capital and UFPE - were selected for standing out in the discussion about the use of waste produced on campus for the biogas generation. Thus, 169 actions in the waste compartment, 111 actions in the energy compartment and 83 actions were listed in the compartment water, were mapped in the 69 institutions surveyed. The five most recurrent actions were: selective waste collection and solid waste (54%), water saving and water control (43%), solar power plant (42%), LED lamp installation (39%) and chemical waste management (39%). It was noticed that 4% of the activities carried out in the waste compartment refer to biogas plants. Finally, studies carried out at UEL and USP showed that preliminary tests were carried out on a bench scale and/or pilot plant in order to assess technical-operational situations for in situ bioenergy generation, that is, for internal energy use generated in the respective universities, estimating the forecast of the potential of biogas and power generation. The UFPE study demonstrated the bioenergy plant implemented on the campus and sought to present the operational units aimed at reproduction in small and medium-sized municipalities. Therefore, it was possible to map the actions that have been carried out in university context, despite the difficulties that these institutions face to consolidate them. Knowing the successful proposals enables continuous improvement, as well as helps and encourages the private sector, society and those HEIs that still do not have consolidated environmental policies, such as UFSCar.
Investigation of sustainability actions in federal public universities in the areas of water, energy and waste
Keywords: Instituições de ensino superior; Água; Bioenergia; Resíduo; Biogás; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA